Estudo de um método de priorização de resíduos industriais para subsídio à minimização de resíduos químicos de laboratórios de universidades - Souza, Karina Elias de (2005)
The majority of the Brazilian universities don t have systematic waste minimization program, especially for chemical laboratory wastes. However, the industries, due to legal responsibilities, economical factors and in order to use waste management as marketing, have been developed waste minimization procedures. This work presents a study of waste prioritization methods to be minimized and applied a industrial method and mathematical model developed by CERCAL (2000), which was adapted to teaching and research chemical laboratories waste of the Chemical Department (DQ) of Universidade Federal de São Carlos. The CERCAL s method covers three type of analysis: economical value, risk and waste minimization capacity. The economical value analysis won t be applied because the University doesn t have cost/benefit control sufficient for the application. The other two analysis were applied using questionnaire answered by technicians, teachers and researchers, where were determined the waste risk and minimization capacity and consequently, its prioritization. Thirteen DQ s laboratories were researched resulting in 107 answers, each one corresponding to one research or teach practice breeder of waste. The wastes were identified and grouped following the place they came from and its chemical likeness, in 27 groups. Among the 27 groups, 12 were classified by the application of the CERCAL s method as essentially priority to be minimized.